GENERATION Z PREFERENCES FOR MENU VARIETY AND RESTAURANT ATMOSPHERE: IMPLICATIONS FOR YOSHINOYA - Dearlyn Astania; Andi Azhar (Suluh Adiluhung Publisher (SAPub), 2025)
This study explores Generation Z's preferences for menu variety and restaurant atmosphere and their implications for Yoshinoya's business strategy. Generation Z tends to favor healthy, diverse, plant-based menu options and comfortable, Instagram-worthy restaurant environments. Yoshinoya needs to adjust its menu, interior design, and digital strategy to remain competitive in this market. This research employs a literature review method by analyzing various relevant sources. The findings reveal that Yoshinoya can enhance its appeal through product innovation, service digitalization, and social media-based marketing campaigns. Additionally, focusing on sustainability and modern restaurant design has the potential to strengthen its relationship with Generation Z. Therefore, strategic adaptation to Generation Z's preferences can create a relevant, engaging dining experience while fostering customer loyalty.